No thermoregulatory or ergogenic effect of dietary nitrate among physically inactive males, exercising above gas exchange threshold in hot and dry conditions. Issue 3 (4th March 2021) - Fowler, Rebecca; Jeffries, Owen; Tallent, Jamie; Theis, Nicola; Heffernan, Shane M.; McNarry, Melitta A.; Kilduff, Liam; Waldron, Mark
Abstract: The aim of this study was to determine the effect of five days dietary nitrate (NO3 − ) consumption on exercise tolerance and thermoregulation during cycling in hot, dry conditions. In a double-blind, randomised crossover design, 11 healthy males participated in an exercise tolerance test (Tlim ) in the heat (35°C, 28% relative humidity), cycling above the thermoneutral gas exchange threshold, after five days of dietary supplementation, with either NO3 – rich beetroot juice (BR; ∼ 9.2 mmol NO3 − ) or placebo (PLA). Changes in plasma [NO3 − ] and nitrite [NO2 − ], core and mean skin temperatures, mean local and whole-body sweat rates, heart rate, perceptual ratings and pulmonary gas exchange were measured during exercise, alongside calorimetric estimations of thermal balance. Mean arterial pressures (MAP) were recorded pre-Tlim . There were no differences in Tlim between conditions (BR = 22.8 ± 8.1 min; Placebo = 20.7 ± 7.9 min) ( P  = 0.184), despite increases in plasma [NO3 − ] and [NO2 − ] ( P  < 0.001) and a 3.8% reduction in resting MAP ( P  = 0.004) in the BR condition. There were no other differences in thermoregulatory, cardio-metabolic, perceptual or calorimetric responses to the Tlim between conditions ( P  > 0.05). Dietary NO3 − supplementation had no effect on exercise tolerance or thermoregulation in hot, dry conditions, despite reductions in resting MAP and increases in plasma [NO3 − ] and [NO2 − ]. Healthy, yet physically inactive individuals with no known impairments in vasodilatory and sudomotor function do not appear to require BR for ergogenic or thermolytic effects during exercise in the heat.